Content Analysis of Iqra' Book for Arabic Learning According to Krippendorff's Perspective - Khitom, Khusnul; Bahy, Moh. Buny Andaru (Journal of Arabic Language Studies and Teaching, 2023)
This research examines the material content of Iqra' book volumes 1 to 6, published by the National LPTQ Research Center "AMM" Yogyakarta Tadarus Team. This study aims to analyze the Arabic language in the book of Iqra' at the level of Aswath Arabiyah learning. The method used by researchers in this research is descriptive qualitative (library research) with data described narratively. The data collection procedure in this study was carried out by reading and understanding the contents of Iqra' book, and the data analysis that the author used was content analysis. Iqra''s book volumes 1 to 6 is a theory used to analyze qira'ah about the Qa'idah Baghdadi technique. The study results show that the al-Ashwat Study is considered a study of Arabic sounds, primarily how Arabic sounds are spoken fluently and clearly, like the owner of the language and how we can understand when Arabic sounds are spoken. Al-Ashwat plays an essential role in dominating listening and speaking skills with the existence of the book Iqra' volumes 1 to volume 6, which contains the title of the book contains procedures for reading the Qur'an in a new way that is not the same as the previous methods, as directed by the technique of Qa'idah Baghdadi.